PROBLEMS OF LEGAL REGULATION OF ADMINISTRATIVE DELIVERY AND DETENTION - Bashlikovs, Maksims (Administrative and Criminal Justice, 2021)
The purpose of this work is to study the problems of legal regulation of administrative delivery and detention in Russian administrative law and the study of possible ways to solve them. This problem is due to the fact that the Code of Administrative Offenses of the Russian Federation. The delivery time is not specified as a measure to secure proceedings on cases of administrative offenses, which is a flaw in administrative legislation and may violate the rights and freedoms of a person and citizen. And the law does not establish the duration of a person’s time in office space and his waiting for the start of legal proceedings which is a serious legislative gap. The novelty of this work lies in the formulation by Autor’s of modern and effective proposals for the revision of individual issues related to measures of administrative proceedings and the reality of solving these problems. The Code of Administrative Offenses of the Russian Federation must be modified accordingly in order to clearly regulate or establish specific time limits for the delivery in police office and the time to wait for the commencement of proceedings. In this paper, the above problems and progressive solutions are discussed in detail.